Can Indonesian Palm Sugar Compete? An Analysis Of Comparative Advantage, Influencing Factors, And Competitive Position - Purnamasari, I Gusti Ayu Agung Jaya; Arisena, Gede Mekse Korri; Susrusa, Ketut Budi; Nurfadillah, Suryani; Prayoga, Kadhung (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2025)
Indonesian palm sugar commodities still face challenges such as household-scale production industries, lack of farmers’ knowledge, and quality standard compliance. There is a need to improve the processing industry and quality to meet national and international standards. This study analyzes and evaluates the competitiveness of Indonesian palm sugar in the international market using secondary data from 1998-2022 with quantitative descriptive statistics methods. Revealed Comparative Advantage (RCA) analysis shows that Indonesian palm sugar was not competitive from 1998 to 2010, with a value of <1, but became competitive from 2011 to 2022 with a value of >1. Error Correction Model (ECM) analysis reveals that factors affecting the competitiveness of palm sugar were export volume and export price, while the exchange rate of Rupiah to US Dollar and Indonesia’s Gross Domestic Product (GDP) per capita had no impact. The competitive position of Indonesian palm sugar using Export Product Dynamic (EPD) shows an average position of falling star, followed by rising star, retreat, and lost opportunity.